INDUSTRIJA 4.0 - ISTRAŽIVANJE KONCEPTA I IMPLIKACIJA ZA POSLOVANJE - Đorić, Žarko; Roganović, Milijana (International Journal of Economic Practice and Policy, 2022)
Big and significant changes at some point are called revolutions. The revolution involves changes in culture, economy and socio-political institutions and, accordingly, it directly affects people’s lives. In that context, Industry 4.0, Industrial Revolution 4.0 or the Fourth Industrial Revolution aimed at creating smart products, procedures, processes and ultimately entire production. Industry 4.0 also produces significant business implications by delivering greater flexibility and robustness along with the highest quality standards in engineering, planning, manufacturing and operational and logistics processes. This will lead to the emergence of dynamic "real-time", self-organizing values that can be optimized concerning various criteria such as cost, availability, and resource consumption. Having in mind the abovmentioned, the paper’s primary goal is to look at the effects and problems of Industry 4.0 from the perspective of the business sphere in a general sense. The findings can be useful to companies (and in our country) that are just beginning when it comes to implementing new technologies that bring a new wave of change. On the whole, given its features and changes, it can be argued that this is the most advanced and sophisticated revolutionary period that completely changes the traditional way of doing business. The results of this research are useful to the creators of industrial and innovation policy because they indicate the state and some of the key directions of change to create conditions for the development of Industry 4.0 digitalization and reindustrialization.